2019
DOI: 10.19173/irrodl.v20i1.3789
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Career Adult Learners in an Online Doctoral Program and the Drivers of Their Academic Self-Regulation

Abstract: Adult professionals enroll in online graduate programs and rely on social support and on their ability to self-regulate to be successful. The literature on academic self-regulation among emerging adults (traditional college age) is ample, but we do not know how social support interacts with academic self-regulation among adult graduate students at mid-career, particularly among those students who are first generation college goers. This study addressed the following questions: (1) To what degree do parental ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
(43 reference statements)
3
12
0
1
Order By: Relevance
“…The study found that RF predict SLS better than TF, particularly the student-faculty relationship. Distance education programs must purposefully develop support systems, such as the cohort model, that encourage connectedness and social integration (Kennedy et al, 2015;Williams et al, 2019). Administrators, faculty, and staff of distance education programs must be prepared to facilitate communication using technology, and understand the importance of timely responses to students at all phases of the doctoral program (Gardner, 2009;Rockinson-Szapkiw et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that RF predict SLS better than TF, particularly the student-faculty relationship. Distance education programs must purposefully develop support systems, such as the cohort model, that encourage connectedness and social integration (Kennedy et al, 2015;Williams et al, 2019). Administrators, faculty, and staff of distance education programs must be prepared to facilitate communication using technology, and understand the importance of timely responses to students at all phases of the doctoral program (Gardner, 2009;Rockinson-Szapkiw et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Third, although the modality of instruction changes, student learning needs based on relationships do not disappear even in online environments. For example, social support from family, friends, and peers has a positive impact on academic self-regulation (Akyol & Garrison, 2011;Williams, Wall, & Fish, 2019) and student learning even in technology-facilitated environments (Gardner, 2009;Garrison, 2007;Lee, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cleveland-Innes and Campbell (2012) further emphasized emotive experience in online learning and defined emotional presence as "the outward expression of emotion, affect, and feeling by individuals and among individuals in a community of inquiry, as they relate to and interact with the learning technology, course content, students, and the instructor" (p. 283). For midcareer adult online learners, social support from family, friends, and peers was found to be predictive of their academic self-regulation (Williams et al, 2019).…”
Section: Community Of Inquiry (Coi)mentioning
confidence: 92%
“…The social justice-oriented argument is also evident in Williams, Wall, and Fish (2019) that shows online doctoral education is more accessible to underserved students where more than 30% of students are the first generation of college graduates than traditional doctoral education (the average percentage of those students in science and engineering doctoral programs is 17%).…”
Section: Diversity and Inequalitymentioning
confidence: 99%